Molluscs associated with a Sardinian deep water population of Corallium rubrum (Linnι, 1758) - CROCETTA, F.; SPANU, M. (Mediterranean Marine Science, 2008)
Molluscan species living in association with Corallium rubrumcolonies are poorly known. Specimens found on the branches of red coral colonies located off Capo Caccia (Alghero – SS, West Sardinia, Mediterranean Sea) were studied by analyzing red coral branches collected at a depth of between 100 and 120 m; their assemblage was made up of 44 species, all belonging to the classes Gastropoda and Bivalvia. Some data on the geographical distribution, ecology, taxonomy and dominance of these species, both alive and dead, are given and the most interesting are commented on. Among the recorded species Trivia multilirata, Simnia purpurea, Coralliophila brevis, Ocinebrina paddeui, Pleurotomella demosia, Palliolum striatum and Pseudamussium sulcatum deserve attention. Moreover, the second finding of living specimens of Asperarca secreta, described only on loose valves, is reported, and finally the prey-predator relationships among several gastropods and Cnidarians are confirmed.